An Evaluation of Antibiotic Prescription Rationality at Lower Primary Healthcare Facilities in Three Districts of South-Western Uganda - Nantongo H; Kiguba R; Batwala V; Mukonzo J (Journal of Multidisciplinary Healthcare, 2022)
Hanifah Nantongo,1,2 Ronald Kiguba,2 Vincent Batwala,3,4 Jackson Mukonzo2 1Department of Nursing, Mbarara University of Science and Technology, Mbarara, Uganda; 2Department of Pharmacology and Therapeutics, Makerere University, Makerere, Uganda; 3Department of Community Health, Mbarara University of Science and Technology, Mbarara, Uganda; 4Directorate of Research and Graduate Training, Mbarara University of Science and Technology, Mbarara, UgandaCorrespondence: Hanifah Nantongo, P.O Box 1410, Mbarara, Uganda, Tel +256 773 413926, Email hnantongo@must.ac.ugPurpose: Antimicrobial resistance is now one of the leading five causes of death globally. This study evaluated the rationality of antibiotic prescriptions at lower primary care levels in three districts of Southwestern Uganda.Methods: This prospective cross-sectional study reviewed 9899 antibiotic prescriptions at 39 health centers following a drug delivery cycle by National Medical Stores in three phases (19 days each on average). Phase 1 started 3 days after delivery, mid-way (Phase 2) and towards the end (Phase 3). The proportion of rationally prescribed antibiotics was determined using a modified criterion by Badar and in reference to Uganda Clinical Guidelines (UCG). Using multivariate logistic regression, the factors associated with rational prescription were determined with 95% confidence intervals.Results: Seven of every 10 antibiotic prescriptions were irrational. Half the prescriptions were made by unauthorized personnel (nurses) and many of the pediatric prescriptions (916, 46.5%) did not bear body weight measurements to guide appropriate dosing. Also, the proportion of rational prescriptions in reference to UCG, 2016 was very low (3387, 34.2%). However, a high proportion of antibiotic prescriptions were legibly written (9462, 95.7%), prescribed by generic names (9083, 91.8%) and had a diagnosis (9677, 97.8%) indicated. Multivariate logistic analysis showed that; availability of medicines (phase 1) (phase 2 AOR=1.14, 95% CI:1.02– 1.28, phase 3, AOR=1.23, 95% CI:1.1– 1.38), legibly written prescription (AOR=0.61, 95% CI: 0.47– 0.78), indication of a date on the prescription (AOR=0.56, 95% CI0.38– 0.81) and being a medical officer were factors associated with rational antibiotic prescription.Conclusion: We observed a high rate of irrational prescription in the study sites and the majority of these were by unauthorized personnel. A review of antibiotic use policies and focused interventions is crucial in these settings.Keywords: inappropriate, antibiotic prescriptions, antibiotic resistance